2005
DOI: 10.1590/s0100-41582005000600009
|View full text |Cite
|
Sign up to set email alerts
|

Virulence pattern of Pyricularia grisea isolates from farmers' fields on newly released upland rice cultivars

Abstract: The virulence pattern of the isolates of Pyricularia grisea from commercial fields of the upland rice (Oryza sativa) cultivars 'Primavera' and 'BRS Bonança' was analyzed. A hundred and seventy monoconidial isolates of the pathogen virulent to 'Primavera' and 139 to 'BRS Bonança' collected from eight fields, during two years (2001-2003) were tested, under greenhouse conditions, on six newly released rice cultivars. Differences in virulence pattern were observed in pathogenic populations of 'Primavera' and 'BRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…where they claimed that Pish, Pi9 and Pita-2 genes were quite ef- The gene-for-gene theory governs disease resistance, where an incompatible reaction occurs between host resistance genes and avirulent pathogen genes (Flor, 1971;Silue et al, 1992). Araújo et al (2005) reported significant variation in the proportion of blast races among different cultivars. The structure of a pathogen population can be significantly influenced by the host population (Chen et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where they claimed that Pish, Pi9 and Pita-2 genes were quite ef- The gene-for-gene theory governs disease resistance, where an incompatible reaction occurs between host resistance genes and avirulent pathogen genes (Flor, 1971;Silue et al, 1992). Araújo et al (2005) reported significant variation in the proportion of blast races among different cultivars. The structure of a pathogen population can be significantly influenced by the host population (Chen et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Araújo et al. (2005) reported significant variation in the proportion of blast races among different cultivars. The structure of a pathogen population can be significantly influenced by the host population (Chen et al., 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study for identifying pathotypes in upland rice, the Brazilian differentials showed greater differential ability than with the international differentials (Silva et al, 2007). The virulence pattern of isolates of P. grisea from commercial fields of widely grown upland rice cultivars Primavera and BRS Bonança was tested by Araújo et al (2005) on six newly released cultivars. These cultivars permitted to differentiate agriculturally important virulence in the pathogen population which can be utilized in selecting breeding lines for specific resistance in blast breeding program.…”
Section: Introductionmentioning
confidence: 99%